Colony size as the main driver of the evolution of song diversity and composition in weaverbirds - Harscouet-Commecy, Erwan; Adenot, Tohi; Thetiot, Alexandre; Bresciani, Nel; Oschadleus, Hans-Dieter; Covas, Rita; Rybak, Fanny; Doutrelant, Claire (Peer Community Journal)

(untitled)
Birdsong is a complex signal shaped by multiple factors and has been explored most widely through the lens of sexual selection, but with mixed results. Here, we focus on the evolution of two song parameters: diversity, which is widely studied, and composition, which is poorly understood. We assessed the potential role of mating system as a proxy for sexual selection, but in addition, investigated whether colony size, a proxy for sociality, and phylogenetic history influence the evolution of these parameters in weaverbirds family (Aves: Ploceidae). Using comparative and path analyses we find that, as expected, species living in larger colonies present greater song diversity and had similar song composition. However, contrary to expectations, polygamous species do not present higher song diversity, nor more similar acoustic composition than monogamous species. A relatively high effect of phylogeny was detected on both song variables. Our results thus suggest that, in this family, sociality is a stronger driver of song diversity and composition than sexual selection. These findings highlight the importance of testing multiple factors when studying bird song evolution and the relevance of sociality.